Corn blotch leafminer Agromyza parvicornis Loew - Gaurav Goyal; Gregg S. Nuessly (EDIS)
EENY-435, a 4-page illustrated fact sheet by Gaurav Goyal and Gregg S. Nuessly, is part of the Featured Creatures collection. It describes this minor and sporadic pest of corn, its distribution, description and life cycle, host plants, economic importance, and management. Includes references. Published by the UF Department of Entomology and Nematology, June 2008.